Aerosolized Silver Nanoparticles in the Rat Lung and Pulmonary Responses over Time. (July 2016) - Silva, Rona M.; Anderson, Donald S.; Peake, Janice; Edwards, Patricia C.; Patchin, Esther S.; Guo, Ting; Gordon, Terry; Chen, Lung Chi; Sun, Xiaolin; Van Winkle, Laura S.; Pinkerton, Kent E.
Silver nanoparticle (Ag NP) production methods are being developed and refined to produce more uniform Ag NPs through chemical reactions involving silver salt solutions, solvents, and capping agents to control particle formation. These chemical reactants are often present as contaminants and/or coatings on the Ag NPs, which could alter their interactions in vivo. To determine pulmonary effects of citrate-coated Ag NPs, Sprague-Dawley rats were exposed once nose-only to aerosolized Ag NPs (20 nm [C20] or 110 nm [C110] Ag NPs) for 6 hr. Bronchoalveolar lavage fluid (BALF) and lung tissues were obtained at 1, 7, 21, and 56 days postexposure for analyses. Inhalation of Ag NPs, versus citrate buffer control, produced significant inflammatory and cytotoxic responses that were measured in BALF cells and supernatant. At day 7, total cells, protein, and lactate dehydrogenase were significantly elevated in BALF, and peak histopathology was noted after C20 or C110 exposure versus control. At day 21, BALF polymorphonuclear cells and tissue inflammation were significantly greater after C20 versus C110 exposure. By day 56, inflammation was resolved in Ag NP–exposed animals. Overall, results suggest delayed, short-lived inflammatory and cytotoxic effects following C20 or C110 inhalation and potential for greater responses following C20 exposure.